Effect of vibration training on neuromuscular output with ballistic knee extensions - Luo, J.; McNamara, B.; Moran, K. (Journal of Sports Sciences, 2008)
The aim of the study was to determine whether vibration applied directly to a muscle-tendon could enhance neuromuscular output during and 1.5 and 10 min after a bout of ballistic resistance training. Fourteen participants were exposed to two training conditions in random order: exercise with vibration and exercise with sham vibration. The exercise comprised three sets of ballistic knee extensions with a load of 60-70% of one-repetition maximum. Vibration (1.2 mm amplitude, 65 Hz frequency) was applied with a portable vibrator strapped over the distal tendon of the quadriceps. Knee joint angular velocity, moment, and power, and rectus femoris and vastus lateralis electromyography root-mean-squared were measured during knee extension. During and after training, the vibration did not induce significant changes in peak angular velocity, time to peak angular velocity, peak moment, time to peak moment, peak power, time to peak power, or average EMG of the rectus femoris and vastus lateralis. We conclude that direct vibration, at the selected amplitude and frequency, does not enhance these neuromuscular variables in ballistic knee extensions during or immediately after training.